Cross-Cultural Aspects of Tourism and Hospitality / A Services Marketing and Management Perspective - Koc Erdogan (Routledge - Taylor & Francis Group, 2021)
This is the first textbook to offer students, lecturers, researchers and practitioners a comprehensive guide to the influence of culture on service providers as well as on customers, affecting both the supply and the demand sides of the industry - organisational behaviour, and the human resource management, and marketing and consumer behaviour. Preface, Acknowledgements, Introduction: International and Global Nature of Tourism and Hospitality, Culture: A Cross-Cultural Intelligence, Culture and Context in Communication, The Influence of Indulgence and Restraint on Tourism and Hospitality, Power Distance as a Cultural Variable, Uncertainty Avoidance as Cultural Variable, Masculinity Versus Femininity and Gender Engalitariasm and Assertiveness,The Influence of Individualism and Collectivism on Tourism and Hospitality, Performance and Humane Orientation as Cultural Variables, Time Orientation as a Cultural Variable, A Review of Trompenaars and Hampden-Turner's Cultural Dimensions, Conclusions, Index.